Effect of Spine Nerves Muscle Stimulation Combined with Scalp Acupuncture on Shoulder-hand Syndrome after Early Stroke - Huazhong YANG; Yongsheng ZHOU; Haipeng JIA; Qingjun YANG; Lingjuan RAO (康复学报)
Objective:To observe the effect of spine nerves muscle stimulation technique(SNMS)combined with scalp acupuncture on early stroke patients with shoulder-hand syndrome(SHS).Methods:A total of 44 patients with shoulder-hand syndrome after early stroke were divided into control group and observation group according to the random number table method, with 22 cases in each group. The control group was treated with scalp acupuncture(The scalp movement area was needled and the midline of the vertex, anterior and posterior oblique line of the parietal of the healthy side were located according to the brain functional area)combined with conventional physiotherapy(included passive joint activity, neural booster and neuromuscular electrical stimulation therapy), 2 hours and 45 minutes per day, 5 days per week. The observation group was treated with spine nerves muscle stimulation combined with scalp acupuncture, 2 hours and 30 minutes per day, 5 days per week. Fugl-Meyer(FMA)of the upper limb motor function, visual analogue scale(VAS)for pain and modified Barthel index(MBI)scores were recorded and compared before and after treatment.Results:There were no significant differences in FMA, VAS and MBI scores between the two groups before treatment(P>0.05).In the control group, the FMA score(27.41±6.82 vs 34.36±8.38, P<0.05), the VAS score(4.27±0.94 vs 2.23±1.23, P<0.05)and the MBI score(29.23±8.21 vs 39.55±9.90, P<0.05)were improved than those at baseline after 4 weeks'treatment. Meanwhile, in the observation group, the FMA, VAS and MBI scores were(43.00±11.50), (0.77±0.37)and(48.00±11.60)respectively after 4 weeks'treatment, which were better than those at baseline(25.05±10.71), (4.45±1.06)and(28.55±6.65), the differences were statistically significant(P<0.05).Moreover, the FMA, VAS and MBI scores in the observation group were significantly better than those in the control group after 4 weeks'treatment(the significant level was P<0.01, P<0.01, P<0.05 respectively).Conclusion:Spine nerves muscle stimulation combined with scalp acupuncture for the treatment of SHS is a safe and effective treatment method. It can provide a scientific basis for accelerating the resolution of pain and provide favorable conditions for functional recovery of upper limbs and hands as well as the recovery of daily living ability, which is worthy of popularization and application.